Developing Students' Activity Through Role Play Method By Using Interview Technique on 11th Grade at SMA Melati Binjai North Sumatera Province - Maitri Ramadhani; Sara Frimaulia; Alwi Musthofa (The Seall Journal, 2020)
This research paper elucidates the effective utilization of role-play as a pedagogical tool to cultivate an immersive experiential learning milieu tailored for postgraduate scholars enrolled in courses focused on comparative evaluation theory and/or evaluation procedures. The integration of meticulously crafted role-play exercises within each of these courses serves to augment the level of student participation, consequently fostering a heightened degree of engagement with the course material. By immersing students in these role-play scenarios, the approach transcends the boundaries of conventional learning, facilitating a profound comprehension of the subject matter through active participation.The intricate role-play exercises outlined within the paper are characterized by their intricate design, ensuring students' active involvement in the learning process. These exercises are strategically developed to propel students beyond the confines of textual analysis, encouraging them to delve into experiential learning. By propelling students to think beyond the mere words they encounter in reading materials, the exercises stimulate critical thinking and creative problem-solving. Furthermore, the experiential nature of the exercises provides a secure environment for students to embrace a "learning by doing" ethos. This not only nurtures their understanding but also cultivates a sense of safety that emboldens them to explore and experiment without the fear of failure. Keywords: roleplay; interview technique